Water and the Gods: Ponds and Fountains in the Hittite State Cult according to Hittite Textual Evidence - Mouton, Alice (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2018)
In the Hittite cuneiform texts, water is considered to be an agent of purification; it is used both for sprinkling and bathing during rituals. The sacred character of water is also attested, since watercourses and springs are divinised and worshipped as members of the Anatolian pantheons. Water deities are numerous in Hittite Anatolia, as are watercourses and springs in the Anatolian landscape.